Pirfenidone treatment of idiopathic pulmonary fibrosis - Ye Gan; Erica L Herzog; Richard H Gomer (Dove Medical Press, 2011)
Ye Gan1,2, Erica L Herzog2, Richard H Gomer31Department of Medicine, Central South University, Changsha, Hunan, China; 2Department of Medicine, Yale University School of Medicine, New Haven, CT, USA; 3Department of Biology, Texas A&M University, College Station, TX, USAAbstract: Idiopathic pulmonary fibrosis (IPF) is a discrete clinicopathologic entity defined by the presence of usual interstitial pneumonia on high-resolution CT scan and/or open lung biopsy and the absence of an alternate diagnosis or exposure explaining these findings. There are currently no FDA-approved therapies available to treat this disease, and the 5-year mortality is ~80%. The pyridone derivative pirfenidone has been studied extensively as a possible therapeutic agent for use in this deadly disease. This review will present the unique clinical features and management issues encountered by physicians caring for IPF patients, including the poor response to conventional therapy. The biochemistry and preclinical efficacy of pirfenidone will be discussed along with a comprehensive review of the clinical efficacy, safety, and side effects and patient-centered foci such as quality of life and tolerability. It is hoped that this information will lend insight into the complex issues surrounding the use of pirfenidone in IPF and lead to further investigation of this agent as a possible therapy in this devastating disease.Keywords: pirfenidone, fibrosis, clinical trials